2017
DOI: 10.1136/jech-2017-209179
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and markers of adiposity among female teachers in Mexico

Abstract: Our findings suggest that SEP remains relevant for adiposity within a single occupational setting and indicate that a stronger conceptualisation of SEP in epidemiological studies may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In addition, it adds a new perspective on our current understanding of the socioeconomic gradient of obesity in women. A number of studies showed evidence of a negative gradient in females, in particular in middle-and high-income countries (Monteiro et al, 2004;Roskam and Kunst, 2008;Dinsa et al, 2012;Hirko et al, 2017;Newton et al, 2017). The negative gradient for females is consistent with the observation that wealthier women have a healthier diet, greater health awareness and more marked preferences for slenderness (Swami, 2015).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, it adds a new perspective on our current understanding of the socioeconomic gradient of obesity in women. A number of studies showed evidence of a negative gradient in females, in particular in middle-and high-income countries (Monteiro et al, 2004;Roskam and Kunst, 2008;Dinsa et al, 2012;Hirko et al, 2017;Newton et al, 2017). The negative gradient for females is consistent with the observation that wealthier women have a healthier diet, greater health awareness and more marked preferences for slenderness (Swami, 2015).…”
Section: Discussionmentioning
confidence: 80%
“…We also assessed internet access at home and the type of insurance women used for serious conditions (public, private or other) as indicators for socioeconomic position. (31) Smoking status was defined as current, ever, never or unknown status. Physical activity was categorized into tertiles of total metabolic equivalent of task per week of multiple-choice frequencies of activity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ethnicity was defined as whether or not women or her parents spoke an indigenous language/dialect. We also assessed Internet access at home and the type of insurance women used for serious conditions (public, private or other) as indicators for socio-economic position (31) . Smoking status was defined as current, ever, never or unknown status.…”
Section: Covariates Assessmentmentioning
confidence: 99%
“…The increasing prevalence of being overweight or obese has become a major global public health problem [1,2], due to health consequences, such as hypertension and type 2 diabetes [3,4], and has attracted the attention of many scholars [5][6][7][8]. Studies on being overweight or obese in developed countries have consistently found a negative relationship between socioeconomic status (SES) and being overweight or obese [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Data from poorer countries show a positive relationship between obesity and SES [8,[12][13][14][15][16][17]. However, in some middle-income countries, there is a negative association between obesity and SES [5,6]. These findings from developing countries reveal that the relationship between SES and obesity is moderated by the level of gross domestic product [15], and this pattern may exists even inside one country [16,17].…”
Section: Introductionmentioning
confidence: 99%